Long-Term Imaging Surveillance of Radiation-Exposed Individuals: Insights from a Singaporean Population - Philippus Hwai; Tony Lee (Sriwijaya Journal of Radiology and Imaging Research, 2024)
Introduction: Radiation exposure, whether occupational, medical, or accidental, carries a potential risk for long-term health complications, including cancer. Long-term imaging surveillance plays a pivotal role in the early detection and management of such complications. This study investigated the outcomes of a long-term imaging surveillance program in a Singaporean population with a history of radiation exposure. Methods: This retrospective cohort study included individuals with documented radiation exposure who underwent long-term imaging surveillance at a major Singaporean healthcare institution between 2000 and 2023. Data on demographics, radiation exposure history, imaging modalities used, and detected abnormalities were collected and analyzed. Results: A total of 352 individuals (mean age 55.2 ± 12.3 years) were included. The most common sources of radiation exposure were medical procedures (62%), followed by occupational exposure (28%), and accidental exposure (10%). The most frequently utilized imaging modalities were computed tomography (CT) scans (75%), followed by magnetic resonance imaging (MRI) (45%), and ultrasound (30%). The overall incidence of detected abnormalities was 18%, with the most common being thyroid nodules (8%), followed by lung nodules (5%), and breast lesions (3%). Early-stage malignancies were detected in 2.5% of individuals. For every 10 Gy increase in radiation dose, the risk of developing severe imaging abnormalities increases by 25% (OR = 1.25, p < 0.001). For every 10-year increase in age at the time of radiation exposure, the risk of severe abnormalities increases by 18% (OR = 1.18, p = 0.023). Individuals with comorbidities (such as diabetes or heart disease) have a 32% higher risk of developing severe imaging abnormalities (OR = 1.32, p = 0.041). Conclusion: Long-term imaging surveillance in radiation-exposed individuals facilitates the early detection of radiation-related complications. This study underscores the importance of tailored surveillance programs based on the type and level of radiation exposure.